Echocardiographic assessment of mitral valve calcification. - Raj, M V (1976)
The mitral valve was assessed by echocardiography in 20 patients, aged 27 to 67 years, who subsequently underwent mitral valve replacement. After removal, the mitral valve cusps were examined by direct measurement, radiography, and quantitative calcium extraction. Increased thickness of the E-F echo was found where calcification or fibrosis was present, differentiation by echocardiography alone being unreliable. However, multiple dense parallel E-F echoes were found in all 10 patients with more than 80 milligrammes of calcium in the valve, while a single thin E-F echo indicated the absence of significant calcification or fibrosis.